Genome-wide siRNA screen of genes regulating the LPS-induced NF-κB and TNF-α responses in mouse macrophages - Li, Ning (Sci Data, 2017)
The mammalian innate immune system senses many bacterial stimuli through the toll-like receptor (TLR) family. Activation of the TLR4 receptor by bacterial lipopolysaccharide (LPS) is the most widely studied TLR pathway due to its central role in host responses to gram-negative bacterial infection and its contribution to endotoxemia and sepsis. Here we describe a genome-wide siRNA screen to identify genes regulating the mouse macrophage TNF-α and NF-κB responses to LPS. We include a secondary validation screen conducted with six independent siRNAs per gene to facilitate removal of off-target screen hits. We also provide microarray data from the same LPS-treated macrophage cells to facilitate downstream data analysis. These data provide a resource for analyzing gene function in the predominant pathway driving inflammatory signaling and cytokine expression in mouse macrophages.